Pengaruh Lokasi, Kepercayaan Dan Kualitas Layanan Terhadap Kepuasan Pelanggan - Hakam Ali Niazi; Agus Sriyanto; Dermawan Chasan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study was to determine the effect of location, trust and service quality on customer satisfaction, namely residents of the Thamrin Residence Apartment in Central Jakarta. In this study, the population is the residents of Apartment Thamrin Residence. The sample in this study amounted to 64 respondents. The data was processed using the help of the SPSS 21 statistical analysis program. The results obtained were that location partially had a significant effect on customer satisfaction, partial trust had no significant effect on customer satisfaction, service quality partially had a significant effect on customer satisfaction at the Thamrin Residence Jakarta Pusat.